2013
DOI: 10.1371/journal.pone.0069299
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Adult Stem Cells in Sustained Lung Injury: A Comparative Study

Abstract: Lung diseases are a major cause of global morbidity and mortality that are treated with limited efficacy. Recently stem cell therapies have been shown to effectively treat animal models of lung disease. However, there are limitations to the translation of these cell therapies to clinical disease. Studies have shown that delayed treatment of animal models does not improve outcomes and that the models do not reflect the repeated injury that is present in most lung diseases. We tested the efficacy of amnion mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 39 publications
3
96
0
1
Order By: Relevance
“…42,43 Furthermore, a first-in-human clinical trial of FM-MSC transplantation for nine patients with steroid-refractory acute GVHD demonstrated that the FM-MSCs appeared safe for intravenous infusion and the overall response rate in severe refractory acute GVHD was similar to that observed when using bone marrow-derived MSCs. 44 This is encouraging because the collection of AMSCs involves procedures less invasive than those used for obtaining MSCs from bone marrow or adipose tissue from donors.…”
Section: Discussionmentioning
confidence: 86%
“…42,43 Furthermore, a first-in-human clinical trial of FM-MSC transplantation for nine patients with steroid-refractory acute GVHD demonstrated that the FM-MSCs appeared safe for intravenous infusion and the overall response rate in severe refractory acute GVHD was similar to that observed when using bone marrow-derived MSCs. 44 This is encouraging because the collection of AMSCs involves procedures less invasive than those used for obtaining MSCs from bone marrow or adipose tissue from donors.…”
Section: Discussionmentioning
confidence: 86%
“…It has been demonstrated that intravenous infusion of human AMSCs ameliorates inflammation and fibrosis in the lung induced by bleomycin in mice [43] and reduces liver fibrosis induced by carbon tetrachloride administration in mice [44].…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyproline assay was used to extrapolate the collagen content and concentration of each segment, as described previously [29,30]. Briefly, frozen lung tissues from each segment were lyophilized to dry weight, hydrolyzed in 6M HCl, and assessed for hydroxyproline content by measuring the absorbance of reconstituted samples (in 0.1M HCl) at 558 nm using a Beckman DU-64 spectrophotometer (Beckman Coulter Inc, Brea, CA).…”
Section: Collagen Concentrationmentioning
confidence: 99%